Immediate reconstruction with autogenous graft after removal of recurrent ameloblastoma, treated 8 years previously - Bonardi, João Paulo; Aita, Tiago Gai; de Lima, Valthierre Nunes; Martins, Thiago Henrique; Pereira-Stabile, Cecilia Luiz; Stabile, Glaykon Alex Vitti; Hochuli-Vieira, Eduardo (ARCHIVES OF HEALTH INVESTIGATION, 2017)
Ameloblastoma is the most common benign odontogenic tumor of the jaw, being most frequently found in the mandible, especially in the body and branch regions. The treatment depends on the aggressiveness of the lesion and if not properly treated, can result in significant morbidity. The objective of this study is to report the case of a 29-year-old patient with a history of ameloblastoma which had been enucleated, recurring after 8 years of evolution. The tumor recurrence was treated through mandibular resection and reconstruction with an iliac crest bone graft. The patient is being monitored and is currently post-operative 50 months, showing no signs of recurrence to date. Ameloblastomas are lesions which present unpredictable behavior and thus require close monitoring irrespective of the treatment. Descriptors: Ameloblastoma; Mandibular Neoplasms; Odontogenic Tumors.